An ecological stance on risk and safe behaviors in children: The role of affordances and emergent behaviors. (January 2015) - Cordovil, Rita; Araújo, Duarte; Pepping, Gert-Jan; Barreiros, João
Abstract: Unintentional injuries are a major cause of disability and death among children. Initial strategies to address child safety issues have primarily either focused on the environment, trying to identify "risk environments", or on the individual, trying to identify "at risk children". More recently, the interaction between child and environment is starting to be addressed in order to enhance the understanding of childhood injuries. The present review suggests a framing of these studies in ecological theory, which implies that children with certain characteristics perceive certain affordances in the environment. In this context, risk may be considered a relational concept. The literature on risk prevention is reviewed and the role of caregivers in managing affordances is emphasized. Highlights: An ecological approach that considers risk as a relational concept is proposed. The role of caregivers in structuring environments for children is highlighted. Managing risk should not impede children's opportunities for exploring and learning.